Strength and stiffness characteristics of unsaturated soils - Nyunt, Than Than (2013)
Strength and stiffness of soils are the most important parameters for geotechnical engineering design. It is widely accepted that stiffness-strain behaviour of soil is highly non-linear and it is therefore important to understand stiffness degradation with strain amplitudes. For unsaturated soils, the relationships between stiffness and strain, and shear strength and strain rate are complicated by the presence of negative pore-water pressure. In Singapore two thirds of the land area is covered by residual soils where the groundwater table is found at some depth. Therefore the residual soils above the groundwater table are unsaturated. Not much research work has been done on stiffness-strain relationship and shear strength with strain rate of unsaturated soils. Laboratory measurement of stiffness at small strains requires local strain measurement device. In this study, local displacement transducers (LDTs) were fabricated in-house following the design of Goto et al. (1991) using a conventional full Wheatstone bridge circuit. An alternative circuit to the Wheatstone bridge circuit, the Anderson loop circuit, was introduced to improve the performance of LDT. LDTs were fabricated in identical fashion but with different circuits. Performances of the LDTs using the full Wheatstone bridge and the Anderson loop circuits were evaluated and discussed in detail. It was observed that the LDT with the Anderson loop circuit was twice as sensitive as the LDT with the Wheatstone circuit. In addition, the LDT with the Anderson loop circuit outperformed the LDT with the Wheatstone bridge circuit in terms of lower deviation, hysteresis and repeatability errors. Triaxial compression tests, bender element tests and resonant column test were performed using different soils (i.e. kaolin, sands and residual soils) to measure stiffness-strain relationship and small-strain stiffness (Gmax) of soils. Stiffness-strain relationships of consolidated kaolin were measured by performing constant water content test (CW) at different initial matric suctions and at different strain rates. Shear stiffness increased significantly with increasing initial matric suctions.